Characterization of a slotted circular patch resonator for adjustable dual-mode dual-band bandpass filters - Zhang, Runqi (2013)
A slotted circular patch resonator is proposed to design a dual-mode dual-band bandpass filter in this work. Three sets of slots are etched into a circular patch. First, four arc-oriented slots are etched to lower the TM01 mode resonant frequency. Then, four radial-oriented slots are etched from the edge of the circular patch to bring down the resonant frequency of the TM21 mode. By changing these two sets of slots, the TM01 and TM21 resonant modes are adjusted to make up the second dual-pole passband. Next, a slot is etched into the center of the circular patch to split the pair of TM11 degenerate modes, which forms the first dual-mode passband. Two high impedance transmission lines are connected to the resonator at a 90° angle along the patch. To increase the out-of-band rejection, two more transmission zeros are introduced by cross-coupling between the input and output feed lines. Two prototype dual-band filters are designed with different frequency ratios so as to verify the design principle. The measured results agree well with the simulated ones.